Math for merchandising a step-by-step approach - Moore, Evelyn C. 1951- (Prentice Hall, 1998)
This book provides a practical application of the skills necessary in a merchandising career. Beginning with number fundamentals, it moves into the skills needed to communicate words into calculators or computers as a means of translating business needs into mathematical answers.Merchandising Math parallels a merchandising career by presenting math in the same sequence as they would be encountered in business. Beginning with the functions of a sales associate (calculating percentage of sales), it progresses to writing orders, calculating markup, analyzing plans, profit and loss statements, and cost sheet development for corporate product development. It provides practical experience with math skills relevant to retail merchandising through charts and templates (T-charts for markup, templates for a six month plan, and profit/loss templates).